Total Health for Children : Every Parent's Guide to Keeping Your Child Well and Knowing What to Do When Illness Strikes - Edited By David Elliman and Helen Bedford (London Marshall, 1999)
Provides information enabling the parent to understand, prevent, and cope with the major health issues that will affect his or her children. The book describes every medical problem that children may suffer from, explains how to prevent it, and suggests various treatments should an illness develop.
Includes Index and Colour Illustration.
Keywords: Children--Health and Hygiene